Penanganan Pesawat Udara Yang Rusak di Bandar Udara - Yuke Sri Rizki (WARTA ARDHIA, 2010)
The airport is a place used by aircraft for landing and take off with all its activities. Therefore to archieve hight flight safety, airport operations must comply with specified procedures. One of the the Soekarno-Hatta airport is numbers of damaged aircraft in the apron area that neglected. Besides reducing the prestige as an international airport, it also disrupts the movement in operation. The purpose of this study is to conduct observations in the hadling of demaged aircraft on airport movement areas. While the benefit is as input to related parties for the aircraft handling. Process and analysis of this study use gualitative methods through detailed description, exposition, and explanation based on primary and secondary data compilation. This paper review the handling of the demaged aircraft the Soekarno-HaIta airport. Expected results of this study may provide solution or recomendation in effort to clean the area from aircraft which no longer operated.